Dose–response relationship of physical exercise interventions for balance performance in children and adolescents with intellectual disabilities: a systematic review and meta-analysis - Gao, Ziqi; Li, Yafan; Wang, Yaxin; Quan, Wei; Meng, Hongnan; Kang, Jianxin (Frontiers in Public Health, 2025)
ObjectiveTo systematically evaluate the impact of exercise interventions on balance performance in children and adolescents with intellectual disabilities and examine the dose–response relationship of key intervention parameters.MethodsA comprehensive search of PubMed, Web of Science, Embase, Scopus, and the Cochrane Library identified eligible randomized controlled trials (RCTs). Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Subgroup analyses and non-linear meta-regression were performed to explore potential effect modifiers and dose–response patterns.ResultsA total of 23 eligible studies comprising 31 datasets and 1,179 participants were included. Pooled analysis showed significant improvement in balance performance [SMD = 0.69, 95% CI (0.48, 0.89), p < 0.001]. Dose–response modeling indicated maximal benefit at approximately 717 MET·min/week (Hedges' g = 0.76). Subgroup analyses revealed greater effects with a frequency of ≥3 sessions/week [SMD = 0.76, 95% CI (0.48, 1.03), p < 0.001], session duration >60 min [SMD = 0.82, 95% CI (0.35, 1.29), p = 0.001], and intervention period < 8 weeks [SMD = 0.78, 95% CI (0.46, 1.10), p < 0.001].ConclusionModerate-dose exercise (717 MET·min/week) can significantly improve the balance performance in children and adolescents with intellectual disabilities, with specific frequency, duration, and intervention period combinations yielding superior outcomes. These findings provide an evidence-based basis for precision health strategies. However, moderate heterogeneity highlights the need for confirmation through larger, multicenter, and long-term trials.